Lipopolysaccharide and Its Analog Antagonists Display Differential Serum Factor Dependencies for Induction of Cytokine Genes in Murine Macrophages - Perera, Pin-Yu (American Society for Microbiology, 1998)
Monocytes/macrophages play a central role in mediating the effects of lipopolysaccharide (LPS) derived from gram-negative bacteria by the production of proinflammatory mediators. Recently, it was shown that the expression of cytokine genes for tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β), and interferon-inducible protein-10 (IP-10) by murine macrophages in response to low concentrations of LPS is entirely CD14 dependent. In this report, we show that murine macrophages respond to low concentrations of LPS (≤2 ng/ml) in the complete absence of serum, leading to the induction of TNF-α and IL-1β genes. In contrast to the TNF-α and IL-1β genes, the IP-10 gene is poorly induced in the absence of serum. The addition of recombinant human soluble CD14 (rsCD14) had very little effect on the levels of serum-free, LPS-induced TNF-α, IL-1β, and IP-10 genes. In contrast, the addition of recombinant human LPS-binding protein (rLBP) had opposing effects on the LPS-induced TNF-α or IL-1β and IP-10 genes. rLBP inhibited LPS-induced TNF-α and IL-1β genes, while it reconstituted IP-10 gene expression to levels induced in the presence of serum. These results provide further evidence that the induction of TNF-α or IL-1β genes occurs via a pathway that is distinct from one that leads to the induction of the IP-10 gene and that the pathways diverge at the level of the initial interaction between LPS and cellular CD14. Additionally, the results presented here indicate that LPS structural analog antagonists Rhodobacter sphaeroides diphosphoryl lipid A and SDZ 880.431 are able to inhibit LPS-induced TNF-α and IL-1β in the absence of serum, while a synthetic analog of Rhodobacter capsulatus lipid A (B 975) requires both rsCD14 and rLBP to function as an inhibitor.